The Role of Leadership in Improving Managerial Accountability at Islamic Higher Education - Siti Mahmudah Noorhayati; Eni Fariyatul Fahyuni (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2024)
This research aims to understand the role of leadership in enhancing managerial accountability at IAI Nasional Laa Roiba Bogor, West Java. Accountability is crucial in ensuring the quality of higher education and involves various aspects such as management, leadership, transparency, efficiency, effectiveness, and participation. Private Islamic higher education institutions face complex challenges, including in infrastructure, financing, academic processes, and the quality of graduates. To achieve this aim, a qualitative approach was employed by involving leaders, faculty, and staff as primary informants. Data collection techniques were carried out through triangulation (combining various sources), and the analysis was inductive. The research results emphasize meaning rather than generalization. The findings indicate that managerial accountability at IAI Nasional Laa Roiba Bogor, West Java is evident in transparency in university management. This is observed through open financial reports, websites, open meetings, and achievement publications. Efficiency and effectiveness in managing educational costs are measured through budget planning, operational cost control, and academic program evaluation.